Knowledge on preconceptional folic acid supplementation and intention to seek for preconception care among men and women in an urban city: a population-based cross-sectional study. Issue 1 (December 2015) - Temel, Sevilay; Erdem, Özcan; Voorham, Toon; Bonsel, Gouke; Steegers, Eric; Denktaş, Semiha
Abstract Background To study the knowledge of a large city population on preconception folic acid supplementation and intention to seek for preconception care within an urban perinatal health program. Methods Cross-sectional surveys run in Rotterdam, the Netherlands, in 2007 and annually from 2009 to 2014. A random sample of residents aged between 16 and 85 years was taken each year from the municipal population register. Bivariate analysis, interaction analysis, trend analysis and logistic regression were performed. Results Knowledge on preconceptional folic acid supplementation significantly improved (+20 %) between 2007 and 2009, and the intention to consult a GP or midwife in the preconception period significantly increased (+53 %) from 2007 to 2012. Logistic regression analyses showed that low socio-economic status was significantly associated with low preconceptional folic acid knowledge, but with higher intention to seek out preconception care. An interaction effect was found between educational level and ethnicity, showing that the higher the educational level the lower the gap of level of knowledge between the different ethnic groups. Conclusion Despite campaigns about folic acid supplementation knowledge on this supplement remains low. The intention amongst men and women to seek out preconception care is still insufficient. Structural interventions to increase and maintain awareness on folic acid supplementation, especially among high-risk groups, are needed.